The Legal Force of The Deed of Wills Regarding Undivided Community Property Which was Canceled Pursuant to State Court Ruling Number 43/PDT.G/2020/PN.MDN - Monica Pratiwi (JILPR Journal Indonesia Law and Policy Review, 2023)
A testamentary deed is the embodiment of a person's last wishes regarding the assets he or she leaves behind. The assets left behind can be inherited and joint assets. The will deed must pay attention to applicable legal rules. In its creation, the testamentary gift deed is closely related to the party authorized to make authentic deeds, namely the Notary profession. This research discusses the legal power of wills regarding joint assets that have not been divided. The problem discussed in this research is how the judge at the Medan District Court considers declaring a Will Deed whose object is joint property that has not been divided, and what are the legal consequences of canceling a Will whose object is joint property that has not been divided. In this case, it refers to the decision of the Medan District Court Number 43/Pdt.G/2020/PN.Mdn. The research method used is normative juridical, descriptive analytical, based on secondary data, through document study searches, with a qualitative approach. From the results of this research, the first conclusion that can be drawn is that the judge's consideration of Deed of Will Number 05 did not clearly take into account the existence of a mixture of assets between the Plaintiff and (the late) Leman as joint search assets with his wife, Mrs. Tan Bie Tju, even though nothing was created between the late Leman and Tan Bie Tju. "marriage agreement", so that the Plaintiff is entitled to ½ (half) of the joint assets. The legal consequences of canceling a Deed of Will whose object is joint property that has not been divided which is canceled by a judge's decision causes the loss of the binding force of the deed on the parties. Notaries should prioritize the principle of prudence by carrying out the obligation to carefully check all documents related to formal correctness before writing them down in the form of a deed.